Baalbek, Libanon. Feldforschungen und Konservierungsarbeiten. Die Arbeiten des Jahres 2020 - van Ess, Margarete; Nàdor, Julia; Burwitz, Henning; Wienholz, Holger (e-Forschungsberichte des DAI, 2021)
In Baalbek, the development of the city from a prehistoric tell to a Roman city and its constant metamorphosis into the early modern period has been the subject of research for many years. Adapting to travel and work opportunities and taking into account the COVID-19 pandemic, fieldwork in Baalbek also took place in 2020, but in several working stages and for a shorter period than planned. Work continued in three areas: with photographic and photogrammetric documentation in the Roman sanctuary of Jupiter, with excavations in the medieval quarter in the so-called Bustan Nassif, and for the preparation of conservation measures in the ›Bustan el-Khan‹ with its public buildings from the Roman period.